EXCLI Journal; 21:Doc30; ISSN 1611-2156 2022
DOI: 10.17179/excli2021-4381
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, time to onset and recurrence of delirium in a mixed medical-surgical ICU population: a secondary analysis using Cox and CHAID decision tree modeling

Abstract: A retrospective secondary analysis of 4,200 patients was collected from two academic medical centers. Delirium was assessed using the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) in all patients. Univariate and multivariate Cox models, logistic regression analysis, and Chi-square Automatic Interaction Detector (CHAID) decision tree modeling were used to explore delirium risk factors. Increased delirium risk was associated with exposed only to artificial light (AL) hazard ratio (HR) 1.84 (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 83 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…Combining the results regarding delirium and subtype assessment tools in knowledge and practice dimensions, we speculate that there is misunderstanding and unfamiliarity in subtype assessment tools among nurses. Additionally, nurses misunderstand (75.1%) delirium prevention and restraint, which is associated with that a retrospective secondary analysis of 4,200 patients in Iran showing that increased delirium risk was associated with exposure to physical restraint application ( 66 ). However, most nurses know about the adverse outcomes and high-risk factors for delirium, which is the same as Xie's survey findings among orthopedic professional nurses and Xu's among ICU nurses ( 59 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Combining the results regarding delirium and subtype assessment tools in knowledge and practice dimensions, we speculate that there is misunderstanding and unfamiliarity in subtype assessment tools among nurses. Additionally, nurses misunderstand (75.1%) delirium prevention and restraint, which is associated with that a retrospective secondary analysis of 4,200 patients in Iran showing that increased delirium risk was associated with exposure to physical restraint application ( 66 ). However, most nurses know about the adverse outcomes and high-risk factors for delirium, which is the same as Xie's survey findings among orthopedic professional nurses and Xu's among ICU nurses ( 59 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Masuyama et al reported the median time and the interquartile range as 3.81 days and 1.81 to 5.79 days in overall, 5.06 days and 3.08 to 8.81 days in the exposure group, and 3.59 days and 1.59 to 4.90 days in the control group in the ICU [ 8 ]. Rahimibashar et al reported the mean time to the recognition of delirium as 7.55 ± 1.88 days in their study conducted in two teaching-hospital ICUs [ 22 ]. Based on Kaplan-Meier curves reported in previous studies, the median time to the onset of delirium from the time of ICU admission is about 3 to 5 days regardless of the study location [ 5 – 9 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“… 14 A CHAID allows one to resolve whole variables and partition consecutive data effectively, and the forward stopping or pruning rules are used to construct decision trees. 15 In this study, we used a CHAID to create a decision tree predictive model, so as to predict the level of functional exercise compliance of patients with breast cancer after surgery.…”
Section: Introductionmentioning
confidence: 99%